Evidencias del mildeo velloso (Peronsclerospora sorghi (W. Weston & Uppal) C.G. Shaw) en cultivos de maíz y sorgo en Colombia - Huertas, C.A.; Sarria Villa, GA; Pineda López, Benjamín (2002)
In the early 1990s, some maize and sorghum plantings along the Colombian Atlantic coast showed plants with characteristic mildew on the leaves, which resembled symptoms caused by Peronosclerospora sorghi. To avoid its dissemination, some regulations were implemented. However, similar symptoms were recently found in the same areas, making it necessary to initiate additional studies to determine the correct etiology of the problem. For this, various areas in the region were surveyed and plants with symptoms were collected for laboratory analysis. Tissue of infected leaves showed a white mycelial growth with downy appearance, chlorotic stripes paralel to the midrib starting at the basis of the leaves, phyllody in the tassel, and leaf-shredding with leaves resembling a whip in sorghum. In the laboratory. samples from Tierralta, Córdoba, showed conidiophores of ap proximately 305 ?, branched, with sterigmata bearing conidias ranging from 25.6 x 20.48? 25.6 x 23.4?, which germinated through a germ tube. In samples from Sincelejo, Sucre, conidiophores varied in length, from 270-340 ?, with a swollen basal cell and a septum at its basis, with conidia between 12.2-21,95 ? (aver. 15.8?) over pointed sterigmata, germinating through germ tubes. Samples collected at Rozo, Palmira, Cauca valley, in forrage sorghum (Sorghum spp) symptoms similar to those found at Sucre and Cordoba, including relatively spheric oospores, with double wall measuring between 33.6-43.2 ?. Based on this survey, it is concluded that the disease present in those crops is sorghum downy mildew, caused by the fungus Peronosclerospora sorghi (Weston & Uppal) Shaw.